ІСТОРІОГРАФІЯ ПЕРШОГО ЗИМОВОГО ПОХОДУ АРМІЇ УНР (Zaporizhzhia Historical Review, 2021)
In the article suggested different assessments of Ukrainian scientists on Winter Campaign of UNR Army are analyses, contradictory aspects of this military march are revealed. The task has been set up to determine the issues having been ignored by researchers until now and which require further disclosing in the scientific literature.